Late preterm birth is a risk factor for growth faltering in early childhood: a cohort study - Victora Cesar G; Barros Aluísio JD; Domingues Marlos R; Matijasevich Alicia; Santos Ina S; Barros Fernando C (BMC, 2009)
Abstract Background Rates of preterm birth are increasing worldwide and this increase is mostly due to infants born between 34 and 36 weeks of gestational age, the so-called "late preterm" births. The aim of this study was to assess the effect of late preterm birth over growth outcomes, assessed when children were 12 and 24 months old. Methods In 2004, all births taking place in Pelotas (Southern Brazil) were recruited for a cohort study. Late preterm (34/0-36/6 weeks of gestational age) and term children (37/0-42/6 weeks) were compared in terms of weight-for-age, length-for-age and weight-for-length z-scores. Weight-for-age, length-for-age and weight-for-length z-scores below -2 were considered, respectively, underweight, stunting and wasting. Singleton newborns with adequate weight for gestational age at birth, successfully followed-up either at 12 or 24 months of age were analyzed and adjusted odds ratios with 95% confidence intervals calculated through logistic regression. Results 3285 births were included, 371 of whom were late preterm births (11.3%). At 12 months, prevalence of underweight, stunting and wasting were, respectively, 3.4, 8.7 and 1.1% among late preterm children, against 1.0, 3.4 and 0.3% among term children. At 24 months, correspondent values were 3.0, 7.2 and 0.8% against 0.8, 2.9 and 0.4%. Comparing with the term children, adjusted odds of being underweighted among late preterm children was 2.57 times higher (1.27; 5.23) at 12 months and 3.36 times higher (1.56; 7.23) at 24; of being stunted, 2.35 (1.49; 3.70) and 2.30 (1.40; 3.77); and of being wasted, 3.98 (1.07; 14.85) and 1.87 (0.50; 7.01). Weight gain from birth to 12 and 24 months was similar in late preterm and term children, whereas length gain was higher in the former group in both periods. Conclusion Late preterm children grow faster than children born at term, but they are at increased risk of underweight and stunting in the first two years of life. Failure to thrive in the first two years may put them at increased risk of future occurrences of serious morbidity in late childhood and of chronic disease development in adult life.